2020
DOI: 10.7199/ped.oncall.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

A 9 months old child with Asymptomatic Bradycardia

Abstract: Complete heart block, AV block clinical problem A 9-month old boy, born of a non-consanguineous marriage was referred for bradycardia. The child was otherwise asymptomatic. On examination, his heart rate was 60 bpm, with no apex pulse deficit. Other systems were normal. Investigations showed complete heart block on electrocardiograph (ECG) and echocardiography was normal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…5 Another case study found a 9-month-old infant experiencing complete AV block without showing symptoms. 2 Children, especially those under three years old, often rely on expressive language inadequate to communicate their feelings, making the diagnosis difficult. Moreover, four-month-old infants can only express their feelings with vocal games.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Another case study found a 9-month-old infant experiencing complete AV block without showing symptoms. 2 Children, especially those under three years old, often rely on expressive language inadequate to communicate their feelings, making the diagnosis difficult. Moreover, four-month-old infants can only express their feelings with vocal games.…”
Section: Discusionmentioning
confidence: 99%
“…1 In children, this disease can go unnoticed by parents due to no visible symptoms. 2 Further, in some instances, it can be detected by chance after a careful physical examination during a visit to healthcare facilities for other diseases. 3 There are several AV block classification degrees.…”
Section: Introductionmentioning
confidence: 99%